2020
DOI: 10.13189/ujer.2020.080402
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Learning Science: Fun in Learning, Interest in Learning Time, Social Implications, Scientific Normality for Science Learning

Abstract: Attitude is the tendency of one's behavior toward an object both positive and negative. Finding out about students in the world of education who can help in the learning process, this study aims to describe the attitudes of students in Muaro Jambi Junior High School 6 and Muaro Jambi Junior High School 5 in terms of 4 indicators, namely enjoyment in learning science, interest in increasing science learning time, social implications of science and scientific normality. The research design used is a mixed method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…The learning objective is to help students learn various knowledge and shape attitudes, behavior, and ways of thinking. Attitude is the tendency of a person's positive or negative behavior towards an object (Sulistioning et al, 2020). A study conducted by Sulistioning et al, (2020) found that to assess student attitudes used indicators of interest because it increased student learning time.…”
Section: Introductionmentioning
confidence: 99%
“…The learning objective is to help students learn various knowledge and shape attitudes, behavior, and ways of thinking. Attitude is the tendency of a person's positive or negative behavior towards an object (Sulistioning et al, 2020). A study conducted by Sulistioning et al, (2020) found that to assess student attitudes used indicators of interest because it increased student learning time.…”
Section: Introductionmentioning
confidence: 99%
“…Fun in learning, interest in learning time, social implications, scientific normality for science learning (Sulistioning et al, 2020), & outdoor learning (Skarstein & Ugelstad, 2020) Learning should not only be in classroom 8 Necessity of media literacy (Anwar et al, 2020) that is embodied in the form of science learning framework online (Opere, 2021), online community (Herodotou et al, 2022), flipped classroom (Shana & Alwaely, 2021), open educational resources (Gerard et al, 2022), use of multimedia (Herianto & Wilujeng, 2021), virtual reality understanding (Hite, 2022), virtual science learning (Telenius et al, 2020), using Edmodo (Ryane & El Faddouli, 2020), animated videos (Nurhayati et al, 2022), motion graphic animation videos (Hanif, 2020), mobile science learning (Chang et al, 2021;Jeno et al, 2020)., VR simulations (Pande et al, 2021) Science learning media must be technologically advanced 9 10 Urgency of cognitive assessment techniques (Darmawan et al, 2020), multiple self-regulated learning measures (Gandomkar et al, 2020), & performance assessment (Yakob et al, 2021).…”
Section: Science Learning Needsmentioning
confidence: 99%